MHD casson nanofluid flow past a wedge with newtonian heating - Ahmad, Kartini; Hanouf, Zahir; Ishak, Anuar (Springer Science + Business Media, 2017)
The problem of steady Casson nanofluid flow past a wedge is studied in this paper. The presence of magnetic field along with Newtonian heating at the surface is considered. The governing partial differential equations are first transformed into a set of nonlinear ordinary differential equations by similarity transformations, before being solved numerically using the Kellerbox method. The effects of the wedge angle from (horizontal plate) to (vertical plate) as well as of as the magnetic parameter M on Ω 0 ∘ 180 ∘ 6/16/2017 MHD Casson nanofluid flow past a wedge with Newtonian heating | SpringerLink https://link.springer.com/article/10.1140%2Fepjp%2Fi2017113565 2/6 1. 2. 3. 4. 5. 6. 7. 8. the nonNewtonian fluid flow and heat transfer characteristics are investigated. It is found that the surface temperature is slightly higher for the flow over a horizontal plate compared to that over a vertical plate. It is also found that the magnetic field decreases the surface temperature but increases the skin friction. The flow of a Newtonian fluid is found to give higher skin friction as compared to that of Casson fluid.